Geographical analysis of industrial development in Rumaitha district for the year 2019 (Journal of the College of Basic Education, 2022)
The natural environment naturally perfectly, the production of raw materials, industrial development instead of exporting them, as industrial production is another productivity in a way that raises its contribution to achieving comprehensive development, and it has been shown that the region possesses the qualifications of geographic industrial development, However, the current industries in the Rumaitha district are small industries dominated by the traditional character, most of which are metal, food, construction and sewing industries, most of which are concentrated in the Rumaitha district center, as it turned out that the number of industrial establishments in the region is close to each other with the presence of superiority of the metal industries, whose number in the district is about 44 industrial units.